Presenting Causal Model of Students' Academic Burnout based on Perfectionism with the Mediating Role of Academic Procrastination and Academic Engagement - Seif, Mohammad Hasan; Talebi, Saeid; Darvishi , Maryam (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this study was examining the relationship between perfectionism and academic burnout with mediating role of academic procrastination and academic engagement in a casual model form among the undergraduate engineering students of Shiraz University during the2014-2015 academic year. Descriptive correlational method was used and out of 120 students were selected via simple random sampling and responded to a questionnaire composed of: Maslash Burnout Inventory (MBI, 2002), Savari Academic procrastination questionnaire (2011), Frost multidimensional perfectionism scale (1990) and Utrecht academic engagement scale (2003). Findings showed that academic burnout had a positive and significant relationship with academic procrastination and maladaptive perfectionism but a negative and significant relationship with adaptive perfectionism and academic engagement. Also it was recognized that perfectionism dimensions had an indirect effect on academic burnout via academic procrastination and academic engagement. Therefore, it is suggested to educators that educate students to choose appropriate criteria according to their abilities and don't lose their self esteem and efforts when they don’t achieve to criteria but they do more efforts to achieve logical goals so that experience less academic burnout and thereupon less procrastinate their academic works and show more academic engagement.